Association between serum endocan levels and organ failure in hospitalized patients with cirrhosis. - Salisa Wejnaruemarn; Sirinporn Suksawatamnuay; Jakapat Vanichanan; Piyawat Komolmit; Sombat Treeprasertsuk; Kessarin Thanapirom (PLoS ONE)
Background & aims Acute-on-chronic liver failure is a syndrome characterized by organ failure and high short-term mortality. The lack of reliable biomarkers for the early detection of acute-on-chronic liver failure is a significant challenge. Endothelial dysfunction plays a key role in the development of organ failure. Serum endocan is a potential new biomarker for endothelial dysfunction. Therefore, this study aimed to assess the association between endocan and organ failure and 28-day mortality in patients with cirrhosis. Methods Hospitalized patients with cirrhosis with and without organ failure were prospectively enrolled according to the criteria of the European Association for the Study of Liver-Chronic Liver Failure consortium. The comparative performances of serum endocan, procalcitonin, and interleukin-6 for diagnosing organ failure and predicting mortality were studied. Results The study included 116 hospitalized patients with cirrhosis, 55 of whom had organ failure on admission. Patients with organ failure had significantly higher endocan, procalcitonin, and interleukin-6 levels than those without it. At a cut-off value of 15.8 ng/mL, endocan showed a sensitivity of 63.6% and specificity of 67.2% for the diagnosis of organ failure, with an area under the receiver operating characteristic curve of 0.65, which is comparable to procalcitonin and interleukin-6. Multivariate analysis identified serum endocan, creatinine, and total bilirubin as independent factors for organ failure in hospitalized patients with cirrhosis. Patients who died within 28 days had significantly higher baseline biomarker levels than those who survived. Liver failure, hospital-acquired infection, mechanical ventilator use, and interleukin-6 ≥37 pg/mL were independent predictors of 28-day mortality. Conclusion Serum endocan is associated with organ failure and is an independent risk factor of organ failure in hospitalized patients with cirrhosis.